Screening of genomic libraries - Novelli, Valdenice M.; Cristofani-Yaly, Mariângela; Bastianel, Marinês; Palmieri, Dario A. [UNESP]; Machado, Marcos A. (Springer Nature, 2013)
Microsatellites, or simple sequence repeats (SSRs), have proven to be an important molecular marker in plant genetics and breeding research. The main strategies to obtain these markers can be through genomic DNA and from expressed sequence tags (ESTs) from mRNA/cDNA libraries. Genetic studies using microsatellite markers have increased rapidly because they can be highly polymorphic, codominant markers and they show heterozygous conserved sequences. Here, we describe a methodology to obtain microsatellite using the enrichment library of DNA genomic sequences. This method is highly efficient to development microsatellite markers especially in plants that do not have available ESTs or genome databases. This methodology has been used to enrich SSR marker libraries in Citrus spp., an important tool to genotype germplasm, to select zygotic hybrids, and to saturate genetic maps in breeding programs. © Springer Science+Business Media, LLC 2013.
Keywords: Enrichment methods; Microsatellites; Molecular markers; genomic DNA; Citrus; codominance; DNA library; expressed sequence tag; gene library; gene mapping; gene sequence; genetic screening; genotype; germplasm; heterozygote; hybrid; microsatellite marker; nonhuman; nucleotide sequence; plant breeding; priority journal; simple sequence repeat; Breeding; Computational Biology; DNA, Plant; Genetic Markers; Genome, Plant; Genomic Library; Microsatellite Repeats